Self-Sustained Flameless Heat Generator Based on Catalytic Oxidation of Methane or Propane-Butane Mixture for Various Object Heating Including Field Heating - Strizhak, P.E.; Soloviev, S.O.; Trypolsky, A.I.; Kirienko, P.I.; Stoliarchuk, I.L. (Science and Innovation, 2024)
An effective catalyst based on ceramic block support with honeycomb structure made of synthetic cordierite with a low coefficient of temperature linear expansion has been developed. Flameless heat generator based on oxidation of methane or propane-butane mixture has been designed. Laboratory and bench trials have showed that the effectiveness of the generator is identical to the foreign analogues. The manufacture of self-sustained flameless heat catalytic generators and catalysts have been launched.